Moonlighting newborn screening markers: the incidental discovery of a second-tier test for Pompe disease. (August 2018) - Tortorelli, Silvia; Eckerman, Jason; Orsini, Joseph; Stevens, Colleen; Hart, Jeremy; Hall, Patricia; Alexander, John; Gavrilov, Dimitar; Oglesbee, Devin; Raymond, Kimiyo; Matern, Dietrich; Rinaldo, Piero
Abstract Purpose To describe a novel biochemical marker in dried blood spots suitable to improve the specificity of newborn screening for Pompe disease. Methods The new marker is a ratio calculated between the creatine/creatinine (Cre/Crn) ratio as the numerator and the activity of acid α-glucosidase (GAA) as the denominator. Using Collaborative Laboratory Integrated Reports (CLIR), the new marker was incorporated in a dual scatter plot that can achieve almost complete segregation between Pompe disease and false-positive cases. Results The (Cre/Crn)/GAA ratio was measured in residual dried blood spots of five Pompe cases and was found to be elevated (range 4.41–13.26; 99%ile of neonatal controls: 1.10). Verification was by analysis of 39 blinded specimens that included 10 controls, 24 samples with a definitive classification (16 Pompe, 8 false positives), and 5 with genotypes of uncertain significance. The CLIR tool showed 100% concordance of classification for the 24 known cases. Of the remaining five cases, three p.V222M homozygotes, a benign variant, were classified by CLIR as false positives; two with genotypes of unknown significance, one likely informative, were categorized as Pompe disease. Conclusion The CLIR tool inclusive of the new ratio could have prevented at least 12 of 13 (92%) false-positive outcomes.